2020
DOI: 10.1186/s12883-020-01840-y
|View full text |Cite
|
Sign up to set email alerts
|

Different predictors after stroke depending on functional dependency at discharge: a 5-year follow up study

Abstract: Background: Level of dependency after a stroke is important for long-term outcome in several aspects, but less is known about important predictors for outcome depending on functional dependency. The aim of the current study was to investigate self-perceived outcome and identify possible predictors of strength, participation, and emotional outcome 5 years after stroke based on functional dependency at discharge from hospital. Methods: This observational cohort study included participants living in Gothenburg th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Most previous cohort studies have suggested that age, prestroke disability, initial stroke severity, education level, diabetes, depression, and other underlying diseases are common factors associated with dependency or disability after stroke. 5,8,9,14,29 Although independence is the most important and meaningful outcome for survivors of stroke, the condition can be associated with various residual impairments that cannot be fully assessed by a single measure. 2,11 Our multivariable regression analysis revealed that nonmodifiable factors of age, comorbidities, and initial stroke severity were associated with all functional domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous cohort studies have suggested that age, prestroke disability, initial stroke severity, education level, diabetes, depression, and other underlying diseases are common factors associated with dependency or disability after stroke. 5,8,9,14,29 Although independence is the most important and meaningful outcome for survivors of stroke, the condition can be associated with various residual impairments that cannot be fully assessed by a single measure. 2,11 Our multivariable regression analysis revealed that nonmodifiable factors of age, comorbidities, and initial stroke severity were associated with all functional domains.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it would be worthwhile to examine whether functional recovery patterns differ by clinical characteristics already known to be associated with stroke prognosis, such as age, stroke type, or stroke severity. 3,4,12,13 Previous stroke outcome studies 5,9,14 examined some early clinical factors associated with 5-year poststroke functional outcomes, although most of them were conducted with relatively few patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among the consequences of the stroke is the reduced ability to return to work (17) . Previous studies have identified that people who did not return to labor were more prone to mood disorders and to experience limitations in family and community interaction, as well as financial problems and dissatisfaction with life, with a consequent decline in HRQoL (17,22) . besides welcoming the singularity that involves the experience of stroke survivors, considering cultures and beliefs, building a comprehensive and individual care plan that benefits the HRQoL of this population segment (10,16) .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic pain had a longer duration of multidisciplinary rehabilitation care (in our sample twice as long as patients without pain) and therefore, more significant care effort also from an economic perspective [ 65 ]. Longer pain duration and higher pain intensity resulted in a longer duration of the rehabilitation care, and it is associated with functional dependency at discharge from hospital, depression, and restricted mobility in the long term [ 66 ]. It is essential that clinicians recognise post-stroke pain earlier to implement all the strategies necessary to avoid its chronification but also to improve HrQoL.…”
Section: Discussionmentioning
confidence: 99%